The Functional Neuroanatomy of Letter-Speech Sound Integration and Its Relation to Brain Abnormalities in Developmental Dyslexia - Richlan, Fabio (Frontiers in Human Neuroscience, 2019)
This mini-review provides a comparison of the brain systems associated with developmental dyslexia and the brain systems associated with letter-speech sound integration. First, the findings on the functional neuroanatomy of letter-speech sound integration are summarized in order to obtain a comprehensive overview of the brain regions involved in this process. To this end, neurocognitive studies investigating letter-speech sound integration in both normal and abnormal reading development are taken into account. The neurobiological basis underlying letter-speech sound integration is consequently compared with existing neurocognitive models of functional and structural brain abnormalities in developmental dyslexia – focusing on superior temporal and occipito-temporal key regions. Ultimately, the commonalities and differences between the brain systems engaged by letter-speech sound integration and the brain systems identified with abnormalities in developmental dyslexia are investigated. This comparison will add to our understanding of the relation between letter-speech sound integration and normal and abnormal reading development.